Dorsal Wrist Carpal Boss Impingement—Dynamic Ultrasound to the Rescue! - Agarwal, Aakanksha; Murray, Timothy E.; Cresswell, Mark; Chandra, Abhishek (Indian Journal of Radiology and Imaging, 2023)
The “carpal boss” is a variant present in 19% of the population according to cadaveric studies but becomes symptomatic in only 1% of cases. With the rising popularity of “yoga,” which includes prolonged hyperextension at the wrist joint with weight bearing, an increasing number of individuals with silent carpal boss present with dorsal wrist pain due to impingement over the dorsal soft tissues by this innocuous bony protuberance. This warrants the attention of radiologists and clinicians while dealing with wrist pain. It can be challenging to identify this bossing on routine radiographs, necessitating special views. We describe the use of dynamic ultrasound in diagnosing “symptomatic” carpal boss, the effects of which become even more evident on imaging during hyperextension—the triggering movement.
Keywords: carpal boss; dynamic ultrasound; impingement